Public Health Insurance and Medical Spending: Evidence from the ACA Medicaid Expansion - Cortnie Shupe (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper investigates the short-run impact of public insurance expansion under the Affordable Care Act on out-of-pocket medical spending (OOP) and risk exposure among low-income, eligible households as well as the incidence of the cost of providing insurance. Using data from the Medical Expenditures Panel Survey (MEPS), I exploit exogenous variation in Medicaid eligibility rules across states, income groups and time. I find that public insurance eligibility reduced mean OOP by 18.2% among targeted households, but it did not causally increase total expenditures among beneficiaries. Rather, Medicaid expansion shifted the burden of payment from eligible households and private insurance (17% reduction) to taxpayers in the form of public insurance (45.7% increase). The efficiency of these public funds can be summarized by a Marginal Value of Public Funds ranging from 0.06 to 0.59 that is highest for households with at least one pre-existing condition.
Keywords: D04; D61; H44; I13; 330; public health insurance; risk protection; MVPF; Medicaid; out-of-pocket expenditures; Affordable Care Act